(untitled) (Justicia &Derecho, 2024)
This article analyses the notion of “neuro-rights” in the following way: first, by interpreting the new final paragraph of article 19 N°1 of the Chilean constitutional text reformed by Law 21.383 that modifies the Fundamental Charter, in order to establish scientific and technological development at the service of people; secondly, by explaining the concerns that constitutional dogmatics has highlighted regarding the regulation and protection of the so-called “neuro-rights”; thirdly, I will make some critical comments on the understanding of the constitutional reform referred to and the articulation of the incipient dogmatic concern for the intersection between technological and legal development.